CREATIVITY OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN FORMING STUDENTS' BEHAVIOR AT KUTTAB AL HUSNAYAIN SURAKARTA - Kumala, Laila Arofah Nur Idha; Sarjono, Joko; Praptiningsih (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2023)
Students are immature individuals or individuals who continue to experience change and development both physically, mentally, and in thought. So it requires help, guidance, and direction from a teacher in shaping behavior as part of the structure of the educational process. The aim of this research is to find out the role of teachers in cultivating Adab and what the supporting and inhibiting factors are. This research uses a qualitative approach. The subjects in this research were PAI teachers and the principal of Kuttab Al Husnayain Surakarta School. Data collection techniques include observation, interviews, and documentation. The analysis technique used is descriptive-narrative. The results of this research show that Islamic Religious Education teachers in Kuttab Al Husnayain play a very important role in cultivating students' manners. The cultivation of manners includes: first, instilling aqidah values where students understand that there is one Almighty God whom we must worship, namely Allah SWT, who understands everything. Everything on earth is God's creation, understanding that the living will definitely die, and the teacher also reminds and always invites you to obey God. Second, instilling the value of worship begins with the habit of praying the dhuha prayer, reading the Koran, praying the midday and asr prayers in congregation, and Friday prayers in congregation. Third, instilling moral values where teachers prioritize an honest attitude towards themselves and others, mutual help, discipline, responsibility, and courtesy towards people around them, whether parents, teachers, or peers.